Rhizofiltration of Heavy Metals (Cadmium, Lead and Zinc) From Fly Ash Leachates Using Water Hyacinth (Eichhornia Crassipes) - Yadav, Amit Kumar; Pathak, Bhawana; Fulekar, M. H. (International Journal of Environment, 2015)
Fly ashes are usually contaminated with toxic heavy metals. These metals are leaching out aftercontact with water during wet disposal system, thus polluting the soil, surface and groundwater. In the present study, a hydroponics experiment was conducted to examine the removalof heavy metals Cd, Pb and Zn by Eichhornia crassipes grown at various concentration of fly ash ranging from 10, 20 and 40 percent over a period of 30 days.After 30 days, the plants were separately harvested, dried and weighedfor biomass of the roots and shoots. The uptake of each metalwas studied in the root and shoot separately, to determine the bioaccumulation of metals in Eichhornia crasspies.The translocation factor was calculated to study the efficiency of the plants forbioaccumulation of each metal in roots and shoot. The results showed that maximum uptake of metals Cd, Pb and Zn by plantwasfoundat the higher concentration (40%) of fly ash.The metals uptake found was 99.16, 166.52 and 741.04 μg g-1 tissues in the roots, respectively and 33.46, 41.33 and 255.90 μgg-1 tissues in the shoots, respectively and successfullyremoved up to 78% of Cd, 82% of Pb and 70% of Zn.The maximum removal efficiency by plant for Cd, Pb and Zn at lower concentration (10%) of fly ash was 84%, 86% and 75%, respectively.The heavy metals accumulated more in roots than in the shoots by Eichhornia crassipes. The maximum bioconcentration factor and translocation factor value of Eichhornia crappies for Cd, Pb and Zn were calculated as 705.55, 705.55 and 614.51 and 41.86, 47.18 and 34.53 respectively. The high removal efficiencies of heavy metals Cd, Pb and Zn was find without toxic effect by this aquatic macrophyte, thisplant can be recommended for the actual treatment of fly ash leachatesin ash pond to clean up the aquatic environment. DOI: http://dx.doi.org/10.3126/ije.v4i1.12187 International Journal of Environment Volume-4, Issue-1, Dec-Feb 2014/15, page : 179-196